A bibliometric review and content analysis of research trends in sensory marketing - Inês Filipa Saraiva Antunes; José Manuel Cristóv\~ao Veríssimo (Cogent Business & Management, 2024)
Despite the numerous studies on sensory marketing, research that holistically reviews through bibliometric and cluster analysis the ensuing knowledge about this topic remains elusive. This study aims to (1) systematically synthesize, condensate and understand the research regarding sensory marketing, and (2) provides suggestions for a future research agenda to help further advances in this field. In detail, based on the methodology proposed by Tranfield et al. (2003), this study was carried out in four different stages: (1) preparation, (2) quality assurance, (3) data extraction, and (4) data analysis and conclusions regarding a systematic review of 342 articles published from 1984 to 2023. Using the Scopus database, the data were retrieved and after processing, the results were graphically illustrated using VOSviewer software. Based on the cluster analysis resulting from the bibliographic coupling analysis, content analysis of 30 documents was performed through the use of MAXQDA software. Overall, this study clarifies the literature that highlights the sensory marketing gaps, enabling the identification of directions for future research.
Keywords: 650; Sensory marketing; five senses; consumer behavior; bibliometric analysis; content analysis